수수 재배시 적용 제초제 선발을 위한 약효 및 약해 평가 - 황재복(Jae-Bok Hwang); 박태선(Tae-Seon Park); 박홍규(Hong-Kyu Park); 김학신(Hak-Sin Kim); 최인배(In-Bae Choi); 구본일(Bon-Il Koo); 배희수(Hee-Soo Bae) (Weed & turfgrass science, 2016)
Herbicide options for weed control in sorghum is very limited, hence there is a need for exploring potential herbicides. Sorghum herbicide tolerance field trails were conducted at two locations, Yaechoun, Gyeongsangbuk-do, and Miryang, Gyeongsangnam-do, in 2013. Tolerance of sorghum was evaluated following the pre-emergence application of methabenzthiazuron 70% (WP), simazine 50% (WP), oxadiargyl 1.7% (EC), and dimethenamid-P 5% + pendimethalin 20% (EC) at the standard rate 157.5 g, 75 g, 5.1 g, and 75 g a.i. $10a^{-1}$, respectively. As well as double the standard rate. On a phytotoxicity scale of 0 to 9, methabenzthiazuron (WP) induced injury to sorghum up to level 1 at the standard rate and to 3 at double the rate, but did not significantly affect the yield any statistical difference from the untreated. Simazine (WP) induced phytotoxicity up to levels 2 and 4 at single and double rates, respectively. Simazine (WP) did not significantly affect yield: however, the values were numerically lower than those in the methabenzthiazuron (WP) treatment. Oxidiargyl (EC) and dimethenamid + pendimethalin (EC) induced no or slight phytotoxicity; however they failed to provide effective weed control at the standard rate (32 and 68% control, respectively). Out of the tested, methabenzthiazuron (WP) was found to have potential for use in sorghum whereas the other herbicides caused unacceptable levels of injury. 수수 재배시 생산비 절감을 위해 몇몇 약제에 대해 약효 및 약해를 검토한 결과 다음과 같은 결과를 얻었다. 수수에 적용이 가능한 제초제로는 약해로 보면, 메타벤즈티아주론(수)은 약해정도가 기준량에서 1, 배량에서 3 정도로 수량에 미치는 영향이 적었다. 그러나 시마진(수)는 기준량에서 2, 배량에서 4로 다소 약해 정도가 높았다. 옥사디아길(유)과 디메테나미드-피 +펜디메탈린(유)는 수수에는 약해가 기준량에서는 1, 배량에서는 3 정도이었으나 잡초방제 효과는 낮았다. 예천과 밀양 2개 지역에서 수량은 메타벤즈티아주론과 시마진 약제에서 각각 $314kg\;10a^{-1}$과 $284kg\;10a^{-1}$로 손제초구 $321kg\;10a^{-1}$, $336kg\;10a^{-1}$로 손제초구와 유의적인 차이가 없었다. 한편, 잡초방제효과는 메타벤즈티아주론(수)는 예천, 밀양 2개 지역에서 각각 95%, 81%로 수수에 적용이 가능한 수준이었다. 그러나 시마진(수)은 2개지역 모두 84%, 79% 이었으며, 옥사디아길(유)과 디메테나미드-피 +펜디메탈린(유)의 방제가는 각각 32%, 68%로 낮았다.